2017
DOI: 10.1038/s41467-017-01390-x
|View full text |Cite
|
Sign up to set email alerts
|

Emergent patterns of collective cell migration under tubular confinement

Abstract: Collective epithelial behaviors are essential for the development of lumens in organs. However, conventional assays of planar systems fail to replicate cell cohorts of tubular structures that advance in concerted ways on out-of-plane curved and confined surfaces, such as ductal elongation in vivo. Here, we mimic such coordinated tissue migration by forming lumens of epithelial cell sheets inside microtubes of 1–10 cell lengths in diameter. We show that these cell tubes reproduce the physiological apical–basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
119
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 66 publications
8
119
0
Order By: Relevance
“…T‐lymphocytes, which exhibit amoeboid migration mode, also do not lift upward on concave surfaces and have been shown to preferentially migrate in concave areas on a sinusoidal wave substrate (wavelength sinusoid 20–160 µm, amplitude 10 µm) . Xi et al demonstrated that epithelial Madin–Darby canine kidney cells (MDCK) can collectively migrate into concave microtubes ( d = 25–250 µm) and form tubular epithelial cell sheets inside the tubes . Maechler et al recently cultured other epithelial cell lines, MDCK and J3B1A, in concave tubes ( d = 269 ± 13 µm or 428 ± 24 µm).…”
Section: Resultsmentioning
confidence: 99%
“…T‐lymphocytes, which exhibit amoeboid migration mode, also do not lift upward on concave surfaces and have been shown to preferentially migrate in concave areas on a sinusoidal wave substrate (wavelength sinusoid 20–160 µm, amplitude 10 µm) . Xi et al demonstrated that epithelial Madin–Darby canine kidney cells (MDCK) can collectively migrate into concave microtubes ( d = 25–250 µm) and form tubular epithelial cell sheets inside the tubes . Maechler et al recently cultured other epithelial cell lines, MDCK and J3B1A, in concave tubes ( d = 269 ± 13 µm or 428 ± 24 µm).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, these epithelioid islands and the budding phenotype on the tumor front may reflect a discrete form of invasion. For example, during renal embryonic development, epithelioid cell clusters collectively migrate during nephric duct elongation, highlighting the migratory potential of epithelioid cells (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…We verify this velocity folding by a simple numerical experiment [ Fig. S1]: we initialize a particle with unit tangent velocity on a triangle mesh surface approximating a spherical surface of unit radius; we use a large 11 integration time step of 2, and after enough folding, the particle moves back to its original position with a negligible error.…”
Section: Algorithmmentioning
confidence: 99%